Pengaruh Psychological Wellbeing dan Perceived Organizational Support Terhadap Job Perfomance dimediasi Job Satisfaction - Wiradanu Aji Pamungkas; Justine Tanuwijaya (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
Abstract. This study aims to analyze the influence of psychological wellbeing and perceived organizational support on job performance mediated by job satisfaction among private bank employees in DKI Jakarta. The sample size in this study was 150 respondents selected using the snowball technique. This study used a quantitative approach with the Structural Equation Model (SEM) AMOS 26 and SPSS 25 mediation testing using the Sobel Test. The results showed that psychological wellbeing had a positive effect on job performance and job satisfaction. Meanwhile, perceived organizational support was also proven to have a positive effect on job performance and job satisfaction. Job satisfaction plays a mediating role between psychological wellbeing and perceived organizational support on job performance. Thus, this study confirms the importance of wellbeing, organizational support, and job satisfaction as the main pillars in improving the performance of banking employees in today's competitive era.